Eosinophilic esophagitis in a girl with pollen allergy who showed trachealization - Himmet Haluk Akar; Eylem Sevinc; Hülya Akgun; Serdal Saadet Özcan; Duran Arslan; Fulya Tahan (Turkish Journal of Gastroenterology, 2019)
-